Comment on “Intravenous Lidocaine Compared with Quadratus Lumborum Block on Postoperative Analgesia Following Laparoscopic Renal Surgery: Protocol for a Randomized Noninferiority Trial” [Response to Letter] - Zhu GH; Hu JH; Peng K (Journal of Pain Research)
Guo-han Zhu,1,2 Jing-hui Hu,1,2 Ke Peng1,2 1Department of Anesthesiology, First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of China; 2Institute of Anesthesiology, Soochow University, Suzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Ke Peng, Department of Anesthesiology, First Affiliated Hospital of Soochow University, 188 Shizi St, Suzhou, Jiangsu, 215006, People’s Republic of China, Tel +86-15962155989, Email pengke0422@163.com